Charge and discharge profiles of repurposed LiFePO4 batteries based on the UL 1974 standard - Hsien-Ching Chung (Nature Portfolio, 2021)
Measurement(s) Charge and discharge profiles Technology Type(s) Two-tier DC load method Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14495604